1990
DOI: 10.1093/geronj/45.3.m82
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle Loss in the Age-Related Decline of Grip Strength: Cross-Sectional and Longitudinal Perspectives

Abstract: The decline of strength with age has often been attributed to declining muscle mass in older subjects. To investigate factors which might influence changes in strength across the life span, grip strength and muscle mass (as estimated by creatinine excretion and forearm circumference) were measured in 847 healthy volunteers, aged 20-100 years, from the Baltimore Longitudinal Study of Aging. Cross-sectional and longitudinal results concur that grip strength increases into the thirties and declines at an accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
342
7
16

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(404 citation statements)
references
References 0 publications
39
342
7
16
Order By: Relevance
“…The present study showed poorer performance in older age groups with a more marked decrease above age 70. This is not only in agreement with cross-sectional studies in Malawi and India (Chilima & Ismail, 2001;Manandhar, 1999), but also with Western longitudinal studies that found a significant decline with age in functional performance, and at an accelerating rate at more advanced ages (Kallman et al, 1990;Grimby, 1995).…”
Section: Handgrip Strengthsupporting
confidence: 87%
“…The present study showed poorer performance in older age groups with a more marked decrease above age 70. This is not only in agreement with cross-sectional studies in Malawi and India (Chilima & Ismail, 2001;Manandhar, 1999), but also with Western longitudinal studies that found a significant decline with age in functional performance, and at an accelerating rate at more advanced ages (Kallman et al, 1990;Grimby, 1995).…”
Section: Handgrip Strengthsupporting
confidence: 87%
“…However, there are data suggesting that the decline in strength with age exceeds the decline in lean mass. Kallman et al (1990), using the Baltimore Longitudinal Study on Aging data, showed that older men have a weaker grip strength, and young men have a stronger grip, than would be predicted by arm muscle mass alone. This ®nding may be partly limited by reliance on anthropometric measures of muscle mass, which are relatively imprecise; data using CT scans are discussed below.…”
Section: Epidemiology Of Sarcopeniamentioning
confidence: 97%
“…Muscle weakness can be caused by aging of muscle fibers and their innervation, osteoarthritis, and chronic debilitating diseases (8). However, a sedentary lifestyle and decreased physical activity and disuse are also important determinants of the decline in muscle strength.…”
Section: Aging and Physical Frailtymentioning
confidence: 99%